2022
DOI: 10.1111/1744-1633.12553
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience of ultrasound‐guided radiofrequency ablation of benign symptomatic thyroid nodules: Safety and short‐term efficacy

Abstract: Aim: To report the safety and short-term efficacy of the use of ultrasound-guided radiofrequency ablation (RFA) for benign symptomatic thyroid nodules. Methods:The treatment outcomes of patients who were treated with RFA for benign symptomatic thyroid nodules from December 2017 to December 2019 were retrospectively reviewed. Nodule volumes were assessed before treatment, and at 1, 6 and 12 months after treatment for comparison. Complications were reported.Results: A total of 18 patients were treated. The volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A review of studies has shown a rate of major complications of 5.6%, which to one in fifteen cases, based on data from a small retrospective study. This suggests that RFA is a reasonably safe procedure that poses only a modest risk of major complications (35). Study by Ho et al reported a complication of pseudocyst formation, Horner syndrome, and thyroiditis.…”
Section: Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of studies has shown a rate of major complications of 5.6%, which to one in fifteen cases, based on data from a small retrospective study. This suggests that RFA is a reasonably safe procedure that poses only a modest risk of major complications (35). Study by Ho et al reported a complication of pseudocyst formation, Horner syndrome, and thyroiditis.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…The occurrence of Horner's syndrome, in this case, could be caused by injury to the middle cervical sympathetic ganglion or compression by hematoma or oedema. The patient was managed conservatively and symptoms improved after 6 months (35).…”
Section: Discussion Discussionmentioning
confidence: 99%